An evaluation of the mixed pediatric unit for blood loss replacement in pediatric craniofacial surgery. Issue 7 (23rd April 2017) - Mogensen, Stefan; Lubenow, Norbert; Nilsson, Pelle; Engquist, Henrik; Knutsson, Folke; Enblad, Per; Nowinski, Daniel; Frykholm, Peter
Summary: Background: Surgical correction for craniosynostosis is often associated with significant perioperative hemorrhage. We implemented a transfusion strategy with a strict protocol including transfusion triggers, frequent assessment of coagulation tests, and the use of a novel transfusion unit, the mixed pediatric unit. Aim: The aim of the study was to evaluate if the applied transfusion strategy could reduce total blood loss and number of blood donors. Methods: Children <1 year old admitted for craniosynostosis surgery were included for the study. On the day before surgery, an adult red blood cell unit was mixed with plasma and split into two mixed pediatric units—one intended for intraoperative use and the other saved for the postoperative period. A series of blood samples were obtained for standard coagulation parameters as well as thromboelastography to evaluate potential coagulopathy. Estimated blood loss, the number of additional standard packed red cell units opened in the first 24 h after surgery, the volume of fluid administered, and the total transfusion volumes were compared to a historical control group with similar age and characteristics. Results: Nineteen infants were included in the study group, and were compared to 21 historical controls. There was a significant reduction of intraoperative transfusion volume. Twelve patients were transfused postoperatively, but in 8 of these additional exposure to packed red cell donor blood was avoided by using the saved mixed pediatric unit. In the historical controls, a total of 10 packed red cell units were used in nine patients postoperatively. No additional transfusions of plasma, platelets, fibrinogen, or tranexamic acid were needed in either group, and the coagulation parameters including thromboelastography remained within their respective normal ranges in the study group. Conclusion: For craniofacial surgery in infants, moderate perioperative blood loss and avoidance of coagulopathy is possible when a multifactorial approach is implemented. In this setting, intraoperative, but not total perioperative blood loss was reduced with the studied protocol. The study indicates that there may be a role for mixed pediatric units to reduce exposure to multiple donors although the reduction in total donor exposure was not significant. Abstract :